Intra-articular platelet-rich plasma injection for the treatment of temporomandibular disorders and a comparison with arthrocentesis - Hancı, Mustafa; Karameşe, Mehtap; Tosun, Zekeriya; Aktan, Tahsin Murad; Duman, Selçuk; Savacı, Nedim (Churchill Livingstone, 2015)
Background: Temporomandibular joint (TMJ) internal derangements are progressive painful conditions and cause joint dysfunction, joint sound, malocclusion, and locking of the mouth. Conservative and invasive techniques can be used for the treatment of TMJ internal derangements. The objective of the present study was to examine the benefit of an intra-articular platelet-rich plasma (PRP) injection and to compare this with arthrocentesis. Methods: Twenty patients (female: male; 15: 5; age 26, 3 +/- 9.3 years) for a total of 32 joints with reducible anterior disc dislocation, as confirmed by Magnetic Resonance Imaging (MRI), were divided into two groups. PRP was used for the study group, and arthrocentesis was used for the control group. Pain intensity, maximal interincisal opening, and TMJ sounds were assessed and compared for evaluation of treatment success. Results: There was a statistically significant reduction in pain intensity and joint sound and an increase in mouth opening in the study group when compared with the control group. Conclusions: This study shows that intra-articular PRP injection for the treatment of reducible disc displacement of the TMJ is a more effective method than arthrocentesis. (C) 2014 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
WOS: 000346833400028
PubMed ID: 25491276
Keywords: Temporomandibular Joint Disorder; Internal Derangement; Platelet-rich Plasma; Arthrocentesis